Keadilan Restoratif dalam Penanganan Anak Pelaku Tindak Pidana di Indonesia: Kajian Psikologi dan Hukum Islam - Sriwiyanti, Sriwiyanti; Saefudin, Wahyu; Aminah, Siti (Journal of Islamic Law, 2021)
Regulations on handling criminal children in Indonesia refer to restorative justice that prioritizes the most beneficial for children’s future. However, the number of child perpetrators of criminal acts whose handling through the judicial process is relatively high. This study aims to describe and analyze the application of restorative justice in Indonesia and acknowledge the psychological conditions and stages of adolescent development involved in criminal acts. In addition, this study also considers from an Islamic Law perspective. This paper is a literature review using legislation, journals, and books as primary data described descriptively. This study reveals that children aged 12-18 years are immature emotionally and cognitively and experience turbulent changes from various aspects that cause children to commit criminal acts. Thus, managing through the diversion mechanism is prioritized over the judicial process. The diversion mechanism regulating juvenile perpetrators of criminal acts aims to restore relationships, children’s best advantages and protect children’s rights based on restorative justice. The author argues that punishment for children must consider the child’s ability to take responsibility for the cases committed, not as revenge for the violations committed.